A construção da gestão compartilhada da reserva extrativista do Mandira, Cananéia, SP - Cardoso, Thaís Almeida (Universidade Federal de São Carlos, 2008)
This study arose from the proposal of fisheries co-management, based on the sharing of decisions and responsibilities between the State, user groups and other local organizations. The research was developed in the Mandira Extractive Reserve, Cananéia, SP, Brazil, with the objective of contextualizing the way of life and use of resources by the beneficiaries and, using the Research-action, to build up the co-management of the Protect Area. The process was developed by the collective action, of a group of local residents and technicians, looking for the involvement of the other beneficiaries for the effective participation in the management of the Mandira Extractive Reserve. We took as a basis for process analysis the management of the oyster (Crassostrea brasiliana), the main resource used by the local residents, which was frightened by super-exploitation. From the structure of the co-management mechanisms in the Protect Area and of the formulation of simple rules, created in a participative way and contextualized to the local reality, we obtained important results, which involved since the empowerment of the community, in search of autonomy and legitimacy, to the recovery of the stock of the oyster in the Reserve. It is important to emphasize that for the consolidation of this process, making it effective along the time and applicable to other fishing resources used inside the Mandira Extractive Reserve, the strengthening of the local organizations, as well as the implementation of other monitoring mechanisms, with the support of the administrating agency, adopting them as public police, should be maintained.
Keywords: Pesca; Pesquisa - ação; Recursos pesqueiros; Manejo pesqueiro; Pesca artesanal; Quilombola; CIENCIAS BIOLOGICAS::ECOLOGIA